Association Between Nurses’ Demographic Characteristics and Knowledge of Healthcare-Associated Infection Prevention: A Cross-Sectional Study - Sulistyowati, Arlina Dhian; Rahmawati, Eka; Agustina, Nur Wulan; Handayani, Sri (Journal of Applied Nursing and Health, 2026)
Background: Healthcare-Associated Infections (HAIs) significantly impact patient safety and healthcare costs. While general knowledge is often reported, evidence regarding how nurses’ demographic characteristics influence HAI knowledge remains inconsistent, particularly in specialised psychiatric settings. This study aims to analyse the relationship between nurses’ characteristics and their knowledge of HAI prevention and control. Methods: This cross-sectional study followed STROBE guidelines. Data were collected from 125 nurses using a total sampling approach. Independent variables included age, gender, education, and length of service, while the dependent variable was knowledge of HAI prevention, measured by a validated 15-item Guttman-scale questionnaire. Data were collected using a validated and reliable structured questionnaire (Cronbach’s alpha > 0.60). Data were analysed using the Contingency Coefficient. Results: Most respondents were aged 30–50 years (84%), female (58.4%), held a Diploma in Nursing (71.2%), and had more than 5 years of service (86.4%). The majority demonstrated good knowledge (94.4%). There were significant relationships between age (p<0.001), education (p<0.001), and length of service (p<0.001) and knowledge of HAI prevention and control. However, no significant association was found between gender and knowledge (p > 0.001). Conclusion: Nurses’ characteristics, specifically age, education, and length of service, are significantly associated with knowledge of HAIs prevention and control, while gender does not show a significant association. These findings emphasise the importance of infection prevention education strategies tailored to nurses’ professional profiles.